Molecular probes for tracking lipid droplet membrane dynamics - Lingxiu Kong; Qingjie Bai; Cuicui Li; Qiqin Wang; Yanfeng Wang; Xintian Shao; Yongchun Wei; Jiarao Sun; Zhenjie Yu; Junling Yin; Bin Shi; Hongbao Fang; et al. (Nature Communications, 2024)
Abstract Lipid droplets (LDs) feature a unique monolayer lipid membrane that has not been extensively studied due to the lack of suitable molecular probes that are able to distinguish this membrane from the LD lipid core. In this work, we present a three-pronged molecular probe design strategy that combines lipophilicity-based organelle targeting with microenvironment-dependent activation and design an LD membrane labeling pro-probe called LDM. Upon activation by the HClO/ClO− microenvironment that surrounds LDs, LDM pro-probe releases LDM-OH probe that binds to LD membrane proteins thus enabling visualization of the ring-like LD membrane. By utilizing LDM, we identify the dynamic mechanism of LD membrane contacts and their protein accumulation parameters. Taken together, LDM represents the first molecular probe for imaging LD membranes in live cells to the best of our knowledge, and represents an attractive tool for further investigations into the specific regulatory mechanisms with LD-related metabolism diseases and drug screening.